Pathophysiology of heart disease : (Lippincott Williams & Wilkins, 1998)
Harvard Medical School, Boston, MA. Textbook on diseases of the cardiovascular system. For medical students and residents. Halftone illustrations. 32 U.S. contributors. Previous edition: c1993. Softcover. DNLM: Heart Disease--physiopathology.